KEANEKARAGAMAN JENIS LICHENES EPIFIT PADA HUTAN KOPI DAN HUTAN CAMPURAN DI NGLIMUT GONOHARJO KENDAL - Senjha Mutiara Asih; Jumari J; Murningsih M (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Wana Wisata Nglimut has the hilly of topograpy land and the high biodiversity. One of which them are many groups of Lichenes. This research aims was to determine the diversity of lichenes species and the diversity of thallus lichenes form in coffee plantation and mixture forest of Wana Wisata Nglimut Gonoharjo. The research was done in coffee forest and mixture forest of Wana Wisata Nglimut Gonoharjo, Kendal, Central Java. Lichenes sampling was done in coffee plantation and mixed forests of Wana Nglimut Gonoharjo, Kendal, Central Java. Sampling was done on by square plot, plot determination of the square plot using purposive method. Results of research on diversity lichenes in Wana Wisata Nglimut Gonoharjo Kendal undertaken in mixed forests and coffee plantation, obtained 42 species of lichenes. Nine species lichenes were found in the coffee plantation, and 41 Lichenes are found in mixed forest, and 8 species found in the coffee plantation and mixed forests. The results showed that the crustose type was the type of thallus lichenes that most commonly found in coffee forest whilest foliose type was lichenes that most commontly found in mixture forest.Keywords: Lichenes Epiphytes, Diversity, Wana Wisata Nglimut